1998
DOI: 10.1074/jbc.273.49.33020
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II Site-directed Alkylation of DNA by Psorospermin and Its Effect on Topoisomerase II-mediated DNA Cleavage

Abstract: Psorospermin, a plant-derived antitumor agent, has been shown to selectively alkylate a guanine at the topoisomerase II cleavage site to trap the topoisomerase II-DNA cleaved complex. The results of this study provide further important insight into the mechanism of the topoisomerase II site-directed alkylation of DNA by psorospermin and its subsequent effects on the topoisomerase II-induced DNA cleavage. First, we demonstrate that the topoisomerase II-induced alkylation of DNA by psorospermin occurs at a time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…This suggests that topoisomerase II -mediated psorospermin alkylation occurs in the initial noncovalent binding step in the topoisomerase II catalytic cycle. We also showed that N7 of guanine is still the alkylation site for psorospermin in the presence of topoisomerase II (10). Furthermore, the topoisomerase II-DNA complex trapped by psorospermin is slowly reversible on the addition of excess salt (10).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…This suggests that topoisomerase II -mediated psorospermin alkylation occurs in the initial noncovalent binding step in the topoisomerase II catalytic cycle. We also showed that N7 of guanine is still the alkylation site for psorospermin in the presence of topoisomerase II (10). Furthermore, the topoisomerase II-DNA complex trapped by psorospermin is slowly reversible on the addition of excess salt (10).…”
mentioning
confidence: 68%
“…We have shown that the enhanced DNA alkylation by psorospermin in the presence of topoisomerase II is dependent on pH but is independent of Mg 2+ or ATP (10). This suggests that topoisomerase II -mediated psorospermin alkylation occurs in the initial noncovalent binding step in the topoisomerase II catalytic cycle.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The intercalation and enhanced covalent alkylation site for psorospermin in the presence of topoisomerase II are within the gate site, with alkylation occurring at the ϩ4Ј position. Finally, psorospermin is a topoisomerase II poison that traps the enzyme-DNA complex, suggesting that psorospermin also may interact with topoisomerase II or, alternatively, distort the DNA on covalent reaction to slow down the religation step (35).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that topo II can be poisoned by various mechanisms. (Liu, Rowe et al 1983;Zechiedrich, Christiansen et al 1989;Frydman, Marton et al 1997;Kwok and Hurley 1998). A mechanism for topo II poisoning was recently discovered in which thiol alkylation of topo II stimulates topo ll-dependent DNA cleavage (Frydman, Marton et al 1997;Wang, Mao et al 2001).…”
Section: Introductionmentioning
confidence: 99%